Pronunciation Difficulties of English Silent Letters: A Study of English Education Students at UIN Raden Intan Lampung - Aryanika, Septa (Journal of Linguistics and Social Sciences, 2026)
Pronunciation plays a crucial role in achieving intelligible spoken communication, particularly for English as a Foreign Language (EFL) learners. However, English orthographic inconsistency, especially the presence of silent letters, often creates significant pronunciation difficulties for Indonesian learners whose first language has a transparent spelling system. This study aims to analyze the types of errors made by first-semester students of the English Education Study Program at UIN Raden Intan Lampung in pronouncing English words containing vowel silent letters ([a], [e], [i], and [u]). This research employed a qualitative descriptive design. Data were collected through pronunciation recordings of 12 selected words and semi-structured interviews. The data were analyzed using Dulay, Burt, and Krashen’s Surface Strategy Taxonomy to classify error types and Brown’s theory to identify error sources. The findings revealed 283 total errors, consisting of addition (55.12%), misformation (32.16%), omission (10.60%), and misordering (2.12%). Addition was the most dominant error, indicating that students frequently pronounced vowel letters that should have been silent. Errors were influenced by interlingual transfer, reliance on spelling, limited phonological awareness, and insufficient pronunciation practice. The study concludes that vowel silent letters remain a significant challenge for pre-service English teachers, highlighting the need for more focused pronunciation instruction in teacher education programs